Anaerobic Decomposition of Domestic Waste from Eggshells, Tea and Coffee Grounds for Organic Fertilizer - Azmin, Muhammad Muaz Bin; Ab Razak, Siti Noraiza; Azman, Muhammad Fazlinuddin; Zulkornain, Muhammad Irfan (Multidisciplinary Applied Research and Innovation, 2022)
The purpose of this project is to produce an organic fertilizer from domestic waste such as eggshells, coffee grounds and tea powder at an optimum ratio. The method used to compost the raw materials into a fertilizer was anaerobic decomposition method. The significance of the project is to reduce groundwater contamination as well as accumulation of salt in soil that will cause a toxic chemicals to the environment through an active used of synthetic fertilizer by farmers. Moreover, such domestic waste are usually stranded rotting which accumulates to greenhouse gases such as methane. The use of an organic fertilizer is an alternative solution to this problem since it can reduce domestic waste pollution and overcome side effects of inorganic fertilizer. Fourier-Transform Infrared Spectroscopy (FTIR) is used to analyse the functional groups of fertilizer and universal pH paper is used to check the pH of soil that grows an okra after fertilization. C-H compound is the main functional group present in fertilizer through FTIR analysis. The best ratio of eggshells, coffee and tea powder is 1:1:1 respectively since it provides neutral pH 7 to soil for okra planting and will cause the okra tree to grow healthier.